Fostering Students' Interest In Learning History Through Agus Salim's Struggle Values During The National Movement - Ardiyanto, Gunawan Fadhil (JURNAL HISTORICA, 2024)
Learning history in the 21st century always experiences various obstacles, one of these obstacles is the lack of interest in learning of students. This problem has become a common problem in history education. For this reason, history teachers must be more professional in teaching history. National hero figures can be used as figures to motivate students. By emulating the attitudes and characteristics of the heroes, it will be useful to shape character and can increase learning motivation. One example of a hero during the struggle for the national movement was K.H. Agus Salim, there are many values and characteristics of his struggle that can be utilized in learning history. Values and characteristics that can be imitated and used as exemplary students are the values of nationalism, and willingness to sacrifice for the nation. This article was written with the aim of cultivating students' interest in learning history through the values of the struggle of K.H. Agus Salim in the period of the national movement. This research method uses qualitative research methods with descriptive research forms and research libraries.